Gender equality in the work of local research ethics committees in Europe: a study of practice in five countries. Issue 2 (30th January 2007) - Moerman, C J; Haafkens, J A; Söderström, M; Rásky, É; Maguire, P; Maschewsky-Schneider, U; Norstedt, M; Hahn, D; Reinerth, H; McKevitt, N
Abstract : Background: Funding organisations and research ethics committees (RECs) should play a part in strengthening attention to gender equality in clinical research. In the research policy of European Union (EU), funding measures have been taken to realise this, but such measures are lacking in the EU policy regarding RECs. Objective: To explore how RECs in Austria, Germany, Ireland, The Netherlands and Sweden deal with gender equality issues by asking two questions: (1) Do existing procedures promote representation of women and gender expertise in the committee? (2) How are sex and gender issues dealt with in protocol evaluation? Methods: Two RECs were selected from each country. Data were obtained through interviews with key informants and content analysis of relevant documents (regulations, guidelines and review tools in use in 2003). Results: All countries have rules (mostly informal) to ensure the presence of women on RECs; gender expertise is not required. Drug study protocols are carefully evaluated, sometimes on a formal basis, as regards the inclusion of women of childbearing age. The reason for excluding either one of the sexes or including specific groups of women or making a gender-specific risk–benefit analysis are investigated by some RECs. Such measures are, however, neither defined in the regulations nor integrated in review tools. Conclusions: The RECs investigated in five European member states are found to pay limited attention to gender equality in their working methods and, in particular in protocol evaluation. Policy and regulations of EU are needed to strengthen attention to gender equality in the work of RECs.